2011
DOI: 10.5152/akd.2011.107
|View full text |Cite
|
Sign up to set email alerts
|

Serum creatinine is independently associated with angiographic extent of coronary artery disease in patients with stable angina pectoris

Abstract: ÖZETAmaç: Renal bozukluğun kardiyovasküler olaylar için yüksek riskle bağlantılı olduğu gösterilmiştir. Kreatinin yüksekliğinin hafif formları bile kötü kardiyovasküler sonuçlarla ilişkilidir. Aşikar renal bozukluğun olmadığı hastalarda kreatinin düzeyleri ile koroner arter hastalığının anjiyografik yaygınlığının ilişkisini araştırmak için retrospektif bir çalışma tasarlandı. Yöntemler: Tipik kararlı anjina pektoris ile Türkiye Yüksek İhtisas hastanesine başvuran ve diyaliz öyküsü olmadan kreatinin düzeyi ≤3 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 20 publications
(32 reference statements)
2
8
0
Order By: Relevance
“…Serum creatinine was shown to be an independent predictor of coronary heart disease mortality in normotensive and normal-weighted survivors of a myocardial infarction but with pre-existing renal disease or heart failure 19. In patients with chest pain undergoing angiography, creatinine correlated with the extent of CAD 20. Consequently, the tested score seems to confirm data from other study groups concerning creatinine.…”
Section: Discussionsupporting
confidence: 81%
“…Serum creatinine was shown to be an independent predictor of coronary heart disease mortality in normotensive and normal-weighted survivors of a myocardial infarction but with pre-existing renal disease or heart failure 19. In patients with chest pain undergoing angiography, creatinine correlated with the extent of CAD 20. Consequently, the tested score seems to confirm data from other study groups concerning creatinine.…”
Section: Discussionsupporting
confidence: 81%
“… 34 Serum creatinine levels have been shown to be an independent predictor of the severity and short-term outcome in patients with coronary artery disease. 31 , 35 , 36 …”
Section: Discussionmentioning
confidence: 99%
“…19 Creatinine was shown to be significantly correlated with both stenosis and extension scores. 19 In this study, vessel score and stenosis score, which are parameters of angiographic severity of CAD, had progressive increasing association with progressively decreasing renal function that is indicated by CCr. So, angiographic severity of coronary artery disease (CAD) is inversely related to CCr level.…”
Section: Discussionmentioning
confidence: 99%
“…Mildly increased serum creatinine is probably a marker for unmeasured proatherogenic factors. 16 In Turkey Korkmaz et al 19 reviewed 892 consecutive patients with typical stable angina pectoris and showed that those in the highest creatinine group (>1.5 mg/dl, but not above 3 mg/ dl) had the highest total stenosis score (17±6, p<0.05) and extension score (78±25, p<0.05) irrespective of age and gender. 19 Creatinine was shown to be significantly correlated with both stenosis and extension scores.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation